2022
DOI: 10.36096/ijbes.v4i4.370
|View full text |Cite
|
Sign up to set email alerts
|

The influence of human resource practices in Islamic perspective on service performance

Abstract: The objective of this study is to examine and analyze the influence of human resource (HR) practices in Islamic perspective on service performance. This study is carried out on Sharia Savings and Loans Cooperatives of Tamzis Bina Utama (TAMZIS) in the DIY Provinces, Indonesia. The data analysis is carried out using quantitative method with Structural Equation Modeling (SEM), and processed with SmartPLS software. The findings in this study indicate that there is a positive and significant relationship in: (1) R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Al-Qosimi found that human resource management in Indonesian waqf savings wallets for the poor is implemented by sharia, both in planning, recruitment, nazir selection, training, development, supervision, performance appraisal, and employee compensation 13 . Fitriana found that recruitment and selection, training and development, and performance appraisal in Islamic perspective positively influence service performance in Sharia savings and loans cooperatives 14 . Rohprihati suggest that Islamic law is the basis for implementing human resource development strategies in Islamic banking institutions, and that regular training is necessary to improve the quality of the workforce 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Al-Qosimi found that human resource management in Indonesian waqf savings wallets for the poor is implemented by sharia, both in planning, recruitment, nazir selection, training, development, supervision, performance appraisal, and employee compensation 13 . Fitriana found that recruitment and selection, training and development, and performance appraisal in Islamic perspective positively influence service performance in Sharia savings and loans cooperatives 14 . Rohprihati suggest that Islamic law is the basis for implementing human resource development strategies in Islamic banking institutions, and that regular training is necessary to improve the quality of the workforce 15 .…”
Section: Introductionmentioning
confidence: 99%